Impact of preoperative chemotherapy as initial treatment for advanced gastric cancer with peritoneal metastasis limited to positive peritoneal lavage cytology (CY1) or localized peritoneal metastasis (P1a): a multi-institutional retrospective study - Yamaguchi, Toshifumi; Takashima, Atsuo; Nagashima, Kengo; Terashima, Masanori; Aizawa, Masaki; Ohashi, Manabu; Tanaka, Ryo; Yamada, Tatsuya; Kinoshita, Takahiro; Matsushita, Hisayuki; Ishiyama, Koshiro; Hosoda, Kei; et al. (Gastric cancer : official journal of the International Gastric Cancer Association and the Japanese Gastric Cancer Association, 2021)
Background Gastric cancer (GC) patients with peritoneal metastasis are defined as stage IV in the Japanese classification of GC. For patients with peritoneal metastasis limited to positive peritoneal lavage cytology (CY1) and/or localized peritoneal metastasis (P1a), gastrectomy followed by S1 monotherapy is one of the most widely accepted therapeutic strategy in Japan. This study investigated the efficacy of preoperative chemotherapy as initial treatment in GC patients with CY1 and/or P1a. Methods We retrospectively reviewed GC patients diagnosed with CY1 and/or P1a at 34 institutions in Japan between 2008 and 2012. Selection criteria were: adenocarcinoma, no distant metastasis except CY1 or P1a, and no prior treatment. The subjects were divided into an Initial-Chemotherapy group and an Initial-Surgery group, according to the initial treatment. Results A total of 824 patients were collected and 713 eligible patients were identified for this study. As the initial treatment, 150 patients received chemotherapy (Initial-Cx), and 563 patients underwent surgery (Initial-Sx). Initial-Cx regimens were cisplatin plus S1/docetaxel plus cisplatin plus S1/others ( n = 90/37/23). Both overall survival (OS) and progression-free survival (PFS) were similar between the Initial-Cx and Initial-Sx groups (median OS 24.8 and 24.0 months, HR 1.07, 95% CI 0.87–1.3; median PFS 14.9 and 13.9 months, HR 1.04, 95% CI 0.85–1.27). The 5-year OS rates were 22.3% in the Initial-Cx group and 21.5% in the Initial-Sx group. Conclusions Although, the preoperative chemotherapy did not show a survival benefit for GC patients with CY1 and/or P1a, initial-Cx showed favorable survival in patients who converted to P0 and CY0.